Analysis of Disaster Survivors' Perceptions Regarding Disaster Preparedness in Tondo Housing - Rasyika Nurul Fadjriah; Arwan; Firmansyah; Sendhy Krisnasari; Khaerunisa (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This study aims to analyze disaster survivors’ perceptions of disaster preparedness in the Permanent Housing (Huntap) area of Tondo, Palu City. Huntap Tondo serves as a relocation site for victims of the 2018 earthquake, tsunami, and liquefaction disasters. Although survivors now reside in a newly developed area designed to enhance safety and comfort, they continue to face potential future disaster risks. Employing a qualitative case study approach, data were collected through in-depth interviews, field observations, and documentation involving 15 key informants, including survivors and community leaders. The findings reveal that survivors’ perceptions of disaster preparedness are strongly influenced by their traumatic experiences, level of understanding of disaster risks, and the availability of disaster information and education within their environment. While some survivors demonstrated high awareness of the importance of preparedness—such as storing emergency supplies and participating in disaster training—others exhibited more passive attitudes, relying predominantly on authorities. Limited community involvement in mitigation planning and insufficient routine socialization were identified as major obstacles to fostering collective preparedness. This study recommends a more participatory, community-based approach alongside strengthening local capacity through ongoing training and the establishment of accessible disaster information systems for all residents of Huntap Tondo.